Predicting ignition delay times of multi-component fuels: empirical mathematical expressions for engineering evaluations; International Journal of Coal Preparation and Utilization; Vol. 45 - Vershinina K. Yu. Kseniya Yurievna; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich; Kuznetsov G. V. Geny Vladimirovich (2025, 2025)
Title screen